2022
DOI: 10.1002/jcb.30340
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA repair to enhance the efficacy of sorafenib in hepatocellular carcinoma

Abstract: The multityrosine kinase inhibitor sorafenib remains an important systemic treatment option for hepatocellular carcinoma (HCC). Signaling pathways, which are targeted by sorafenib, are involved in checkpoint and DNA repair response, RAD51 being a candidate protein. Here, we aim to evaluate the effect of the human RAD51 inhibitor B02 in combination with sorafenib in human HCC cells. Impact of RAD51 expression on HCC patient survival was evaluated by an in silico approach using Human Protein Atlas dataset. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…The details of how sorafenib affects homologous recombination and RAD51 protein expression need further investigation. Recently, Samadaei et al reported that B02, another RAD51 inhibitor, in combination with sorafenib significantly enhanced the efficacy of sorafenib in reducing the cell viability, colony formation ability, and invasion capacity of HCC cells [38]. These findings are in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The details of how sorafenib affects homologous recombination and RAD51 protein expression need further investigation. Recently, Samadaei et al reported that B02, another RAD51 inhibitor, in combination with sorafenib significantly enhanced the efficacy of sorafenib in reducing the cell viability, colony formation ability, and invasion capacity of HCC cells [38]. These findings are in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%